Initiative for Heavily Indebted Poor Countries (HIPC) and Multilateral Debt Relief Initiative (MDRI) : Status of Implementation. (Policy Papers; Policy Paper ;, 2006)
This report reviews progress and issues in implementing the enhanced Heavily Indebted Poor Countries (HIPC) Initiative and reports on the implementation of the Multilateral Debt Relief Initiative (MDRI) by IDA, the IMF, and AfDF. It concludes that the volume of debt relief has increased significantly since the inception of the HIPC Initiative in 1996, thereby reducing HIPCs' debt service burdens and allowing them to finance increased poverty reduction efforts. It also provides updated information on the costs of debt relief under the HIPC Initiative and the MDRI. Finally, it reviews the status of creditor participation and delivery of debt relief under the two initiatives, highlighting the challenges to increase the participation by non-Paris Club official bilateral and commercial creditors in the HIPC Initiative.